Does going cashless make you tax-rich? Evidence from India's demonetization experiment - Satadru Das; Lucie Gadenne; Tushar K. Nandi; Ross Warwick (Queen Mary University of London, School of Economics and Finance, 2022)
This paper investigates the effect of electronic payment technology on tax compliance in a large developing economy. We consider India's demonetization policy which, by limiting cash availability, led to a large increase in the use of electronic forms of payments. Using administrative data on firms' tax returns and variation in the strength of the demonetization shock across local areas, we find that greater use of electronic payments leads to firms reporting more sales to the tax authorities. Our estimates imply that the shift to electronic payments increased reported sales by 5% despite demonetization's negative effect on economic activity.
Keywords: H26; O23; H25; 330; tax compliance; electronic payments; demonetization